2022
DOI: 10.3389/fvets.2022.784387
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequence and Interaction Analysis in the Production of Six Enzymes From the Three Bacillus Strains Present in a Commercial Direct-Fed Microbial (Norum™) Using a Bliss Independence Test

Abstract: The three Bacillus strains present in Norum™ were initially selected by their excellent to good relative enzyme activity (REA) production score for amylase, protease, lipase, phytase, cellulase, β-glucanase, and xylanase. Further studies confirmed that the three isolates also showed an antibacterial activity, Gram-positive and Gram-negative poultry pathogens. Norum™ (Eco-Bio/Euxxis Bioscience LLC) is a Bacillus spore direct-fed microbial (DFM). The Bacillus isolates were screened and selected based on in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(63 reference statements)
1
5
0
Order By: Relevance
“…The microbiota produces various digestive enzymes, such as protease, lipase, and cellulase [74]. We analyzed the rumen digestive enzymes and found that the activities of protease, lipase, and cellulase in the rumen fluid of finishing cattle were significantly increased after feeding with PFDG, which was consistent with the results of previous studies showing that feeding with probiotics and probiotic fermentation products can promote the animal digestive enzyme activity and improve the efficiency of the digestion and absorption of nutrients [75,76].…”
Section: Discussionsupporting
confidence: 87%
“…The microbiota produces various digestive enzymes, such as protease, lipase, and cellulase [74]. We analyzed the rumen digestive enzymes and found that the activities of protease, lipase, and cellulase in the rumen fluid of finishing cattle were significantly increased after feeding with PFDG, which was consistent with the results of previous studies showing that feeding with probiotics and probiotic fermentation products can promote the animal digestive enzyme activity and improve the efficiency of the digestion and absorption of nutrients [75,76].…”
Section: Discussionsupporting
confidence: 87%
“…The authors found that combination of B. amyloliquefaciens and B. licheniformis had more beneficial effects related to their enzyme activity and antibacterial ability when compared all three strains combined. These observations suggested that that while the above mentioned bacterial species are beneficial, additional research is needed to use mixtures of probiotic bacterial species to evaluate their combined synergistic effects to maximize gut health as well as antimicrobial benefits in chickens [81].…”
Section: Bacillus Speciesmentioning
confidence: 99%
“…Flavonoid glycosides are natural compounds that have antioxidant and anti-inflammatory properties, but they can also induce oxidative stress and organ damage when ingested in excess. The Bacillus -based DFM used in this study, Norum™ (Eco Bio/Euxxis Bioscience LLC, Fayetteville, AR), is a spore-based DFM culture consisting of three Bacillus strains: Bacillus subtilis , B. amyloliquefaciens , and B. licheniformis with a stable Bacillus spore content of ~3 × 10 11 spores/g ( 22 ). These Bacillus strains can produce various enzymes (xylanase, cellulase, phytase, lipase, protease, and β-glucanase) that can improve the digestibility and nutrient availability of the feed, as well as modulate the intestinal microbiota and enhance the gut health and immunity of poultry ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Norum™ was sourced from Eco-Bio/Euxxis Bioscience LLC and added to feed at 0.1 g/kg for experimental groups. The Bacillus strains within Norum™ were identified through whole-genome sequencing as Bacillus subtilis (AM1002), Bacillus amyloliquefaciens (AM0938), and Bacillus licheniformis (JD17) ( 22 ).…”
Section: Methodsmentioning
confidence: 99%